(untitled) (Revista Torreón Universitario, 2022)
In the present work, study habits, level of motivation, resources, activities, and learning strategies and their relationship with academic failure in university students of the UNAN – Managua in times of COVID – 19 were analyzed. The study is descriptive, and correlational, according to the time of occurrence of the facts and record of the information, it is prospective. We analyzed 459 online surveys, using Google Forms, to students of the UNAN – Managua. It was determined by Pearson’s correlation test, a P value = 0.745, which turns out to be higher than the critical level of comparison α = 0.05, showed that there is no statistically significant relationship between the hours of study with the academic failure of students. Kramer’s Phi and V association test determined a P value = 0.027, being lower than the critical level of comparison α = 0.05, demonstrating a statistically significant association between learning strategies and academic failure. The technique of multivariate analysis of multiple correspondences showed that students who make use of interactive videos and summaries tend to have fewer failed subjects in contrast to those who use other self-learning strategies. Therefore, it is concluded that the use of didactic and interactive self-learning strategies such as videos, summaries, or outlines, are associated with the achievement of better results than the hours of independent study, or the level of motivation of the students; contributing to reducing the rates of academic failure.